Ethnic Fractionalization, Ethnic Polarization, and Potential Conflict in Parent Districts of IKN - I Ketut Gunawan (Universitas Pendidikan Ganesha, 2024)
The purpose of this research is to determine the degree of ethnic fractionalization and polarization in the parent districts of the new Indonesian Capital of Nusantara (IKN), namely Kutai Kartanegara (Kukar) and North Penajam Paser (PPU) Districts, and assess the potential of ethnic conflict. The research involves quantitative analysis, where statistical formulas are used to calculate the ethnic fractionalization index (EFI) and ethnic polarization index (EPOI). The 2010 BPS population census, the most recent census based on ethnicity, is the primary data used for the core analysis. The study results reveal that both districts have a high level of ethnic diversity, with Kukar having a higher EFI than PPU (0.80 versus 0.75). However, PPU has a greater potential for conflict, as it has a higher EPOI (0.66) than Kukar (0.59-0.60). Considering the socio-political situation, the condition of ethnopolitics in Kukar is relatively conducive to providing support for the IKN development. In PPU, its ethnopolitical climate appears favorable for supporting the development of IKN. However, it is crucial to pay due attention to the issue of indigenous Paser people in IKN, as they represent the third largest ethnic group in Rings 1 and 2 of the IKN areas.